(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Postpartum hemorrhage (PPH) is the leading cause of maternal mortality in low- and middle-income countries. Uterine atony accounts for 70–80% of PPH cases. Management of PPH is usually based on a cascade beginning with the use of uterotonics and eventually hysterectomy in cases of refractory PPH. Different compression suture techniques have been described and used for the management of uterine atony where medical management is insufficient and preservation of fertility is desired. Case presentation: This is a series of four patients who presented to our facility and consequently developed uterine atony that was unresponsive to medical management during cesarean delivery despite the use of multiple uterotonics. All four patients had established risk factors for uterine atony, including induction of labor, augmentation of labor, chorioamnionitis, or fetal macrosomia. Hayman compression sutures were performed in all four patients with success. Estimated blood loss in the series ranged from 400 to 1200 mls. All patients recovered well with no complications reported during the postpartum period. Conclusion: Hayman compression sutures offer an alternative to the more ubiquitous B-Lynch suture with several advantages, including ease of placement and no need for a hysterotomy in PPH post vaginal birth or placement post repair of hysterotomy in cesarean cases. Thus, the may be easier to perform for junior health care professionals as well as in stressful situations.